2014
DOI: 10.1021/tx500312g
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phase I Metabolism of cis-Zearalenone

Abstract: The present study investigates the in vitro phase I metabolism of cis-zearalenone (cis-ZEN) in rat liver microsomes and human liver microsomes. cis-ZEN is an often ignored isomer of the trans-configured Fusarium mycotoxin zearalenone (trans-ZEN). Upon the influence of (UV-) light, trans-ZEN isomerizes to cis-ZEN. Therefore, cis-ZEN is also present in food and feed. The aim of our study was to evaluate the in vitro phase I metabolism of cis-ZEN in comparison to that of trans-ZEN. As a result, an extensive metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In vitro experiments conducted on phase I metabolism of cis -ZEN in human and rat liver microsomes showed that the metabolic pathway of this form may be similar to that of trans -ZEN. α- cis -ZEL, produced during the metabolic pathway of cis -ZEL, may exhibit higher oestrogenicity than its isomer [ 169 ]. Although the estrogenic properties of ZEN are well described, much less is known on their interactions with other nuclear receptors.…”
Section: Toxicological Propertiesmentioning
confidence: 99%
“…In vitro experiments conducted on phase I metabolism of cis -ZEN in human and rat liver microsomes showed that the metabolic pathway of this form may be similar to that of trans -ZEN. α- cis -ZEL, produced during the metabolic pathway of cis -ZEL, may exhibit higher oestrogenicity than its isomer [ 169 ]. Although the estrogenic properties of ZEN are well described, much less is known on their interactions with other nuclear receptors.…”
Section: Toxicological Propertiesmentioning
confidence: 99%
“…Cis-isomerisation of ZEN has been described to occur in the field as an effect of sunlight (Drzymala et al, 2014). As the current analytical methods do not include cis-ZEN, occurrence data in feed or raw material are still not available.…”
Section: Occurrence Of Modified Forms Of Zen In Feed From Plant Originmentioning
confidence: 99%
“…In order to widely estimate the effect of human metabolism on the activity of cis-ZEN, several computed metabolites and the phase-I human metabolites resolved so far (i.e. a-and b-cis-zearalenol) (Drzymala et al, 2014) have been analyzed herein for the capability to interact with the active conformation of ERa-LBD. Several phase-I metabolites retained the structural requirements for interacting with the pocket of ERa, thus pointing out a possible relevant xenoestrogenicity of cis-ZEN in vivo.…”
Section: Introductionmentioning
confidence: 99%